1998
DOI: 10.1042/bj3330175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Pi on the renal Na+-dependent Pi transporter NaPi-2 in thyroparathyroidectomized rats

Abstract: Dietary Pi and parathyroid hormone (PTH) are two most important physiological and pathophysiological regulators of Pi re-absorption in the renal proximal tubule. Effects of dietary Pi on Na+/Pi co-transporter NaPi-2 were investigated in thyroparathyroidectomized (TPTX) rats. NaPi-2 protein and mRNA in the kidney cortex of TPTX rats were increased approximately 3.8- and 2.4-fold in amount respectively compared with those in the sham-operated animals. Administration of PTH to the TPTX rats resulted in a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…An important regulator of Ca and P homeostasis is the activation of 1,25(OH) 2 D 3 by CYP27B1 in the kidney. The expression of CYP27B1 has been shown to be regulated by dietary P, PTH, and 1,25(OH) 2 D 3 (Gonzalez and Martin, 1996;Takahashi et al, 1998;Kawane et al, 2001;Mulroney et al, 2004). With the greater circulating concentrations of 1,25(OH) 2 D 3 observed among our PD animals, it was not surprising that we observed a similar increase in renal expression of CYP27B1 mRNA.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…An important regulator of Ca and P homeostasis is the activation of 1,25(OH) 2 D 3 by CYP27B1 in the kidney. The expression of CYP27B1 has been shown to be regulated by dietary P, PTH, and 1,25(OH) 2 D 3 (Gonzalez and Martin, 1996;Takahashi et al, 1998;Kawane et al, 2001;Mulroney et al, 2004). With the greater circulating concentrations of 1,25(OH) 2 D 3 observed among our PD animals, it was not surprising that we observed a similar increase in renal expression of CYP27B1 mRNA.…”
Section: Discussionsupporting
confidence: 65%
“…Although this has not been reported previously, a possible explanation for the increased expression is that the suppression of PTHR expression by PTH (Gonzalez and Martin, 1996;Kawane et al, 2001) would likely not take place with the very low concentrations of circulating PTH seen at the end of this study. In addition to increases in the message for CYP27B1, levels of NPT2 mRNA have been shown to be dramatically increased during P deficiency (Takahashi et al, 1998;Mulroney et al, 2004). We did not see an increase in the expression of this gene based on dietary P restriction.…”
Section: Discussionmentioning
confidence: 99%
“…The protocols for these studies were approved by the Animal Experimentation Committee of Tokushima University. The effect of PTH on regulation of type IIc Na-P i cotransporter in TPTX rats was investigated after intravenous administration of bovine PTH (amino acid 1-34; Sigma) at a dose of 7.5 g/100 g body wt under anesthesia (14,27).…”
Section: Animals and Dietsmentioning
confidence: 99%
“…The changes in PTH levels were achieved within at least 4 hrs after switching to high Pi intake and within less than 2 hrs after ingesting low phosphate diets. Previous experiments in thyroparathyroidectomized rats showed that adaption from high to low Pi diet did not increase NaPi-IIa abundance within 4 hrs whereas switching from low to high Pi reduced NaPi-IIa protein after 4 hrs [55]. Since animals were not substituted with thyroid hormone no conclusions on the adaption from high to low Pi diets can be made.…”
Section: Napi-iia Is Upregulated Despite Persistently High Fgf23 Levelmentioning
confidence: 94%